2018
DOI: 10.1080/15592324.2018.1477905
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of sulfur with phytohormones and signaling molecules in conferring abiotic stress tolerance to plants

Abstract: Sulfur (S) is a macronutrient for the plant, which has an immense role in basic plant processes and regulation of several metabolic pathways. It has also a major role in providing protection against adverse conditions. Sulfur-containing amino acids and metabolites maintain plant cell mechanisms to improve stress tolerance. It interacts with several biomolecules such as phytohormones, polyamines, nitric oxide (NO), and even with other plant nutrients, which can produce some derivatives those are essential for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 52 publications
1
64
0
Order By: Relevance
“…This is particularly true for S as drought stress results in low SO 4 2− absorption and its subsequent translocation to leaves that also limits NO 3 − translocation, consequently reducing nitrogen use efficiency 39 . Similarly, S-deprivation influences K accumulation in shoots providing evidence that K + acts as counter-cation in the absence of SO 4 2− in leaf tissue 24,40 . The results in present study showed that low water availability considerably www.nature.com/scientificreports www.nature.com/scientificreports/ (P < 0.01) restricts NPK accumulation in shoots of maize seedlings (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…This is particularly true for S as drought stress results in low SO 4 2− absorption and its subsequent translocation to leaves that also limits NO 3 − translocation, consequently reducing nitrogen use efficiency 39 . Similarly, S-deprivation influences K accumulation in shoots providing evidence that K + acts as counter-cation in the absence of SO 4 2− in leaf tissue 24,40 . The results in present study showed that low water availability considerably www.nature.com/scientificreports www.nature.com/scientificreports/ (P < 0.01) restricts NPK accumulation in shoots of maize seedlings (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…It promotes biogenesis of chloroplast by delivering Mg, Fe, Zn and Mn ions and improves CO 2 fixation as reported in Spinacea oleracea (Chen et al ). Moreover, the antioxidant enzyme activities such as SOD, CAT, APX, GPX was up regulated in stressed cucumber on NaHS treatment (Hasanuzzaman et al ). The H 2 O 2 and lipid peroxidation levels were also decreased showing H 2 S induced protection of crops against salt stress (Kaya et al ).…”
Section: Salt Stress Responsive Genes Regulated By H2smentioning
confidence: 99%
“…These genes are involved in regulating signal transduction and oxidative stress and finally confer tolerance to the plants (Ye et al ). Literature supports that H 2 S interacts with various signaling molecules such as ABA, gibberellic acid and ethylene and modulates their signaling pathway (Wojtyla et al , Banerjee et al , Hasanuzzaman et al 2018a, b). Mechanistically H 2 S provides sulfur to modify the thiol group (‐SH) of cysteine to produce, persulphide adducts (‐SSH) (Aroca et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (, b) reported that H 2 S functions not only downstream of NO signaling, but also acts downstream of salicylic acid‐induced heat tolerance signaling pathways (Li et al ). Post‐harvest ripening and senescence in banana could be alleviated by H 2 S by countering oxidative stress along with the antagonizing effect of ethylene signaling (Ge et al , Hasanuzzaman et al ). On the other hand, H 2 S was found to act upstream of NADPH oxidase (RBOH1) and H 2 O 2 accumulation, governing the tomato root morphogenesis (Mei et al ).…”
Section: Interplay Between H2s and No Signaling Pathwaysmentioning
confidence: 99%